Prolificacy and Pre-Weaning Mortality of West African Dwarf Sheep Raised Intensively in a Hot Humid Environment - , P. C. Jiwuba; , F. O. Ahamefule; , K. Ikwunze; , E. M. Assam (Archives of Current Research International, 2016)
The production records of a flock of West African Dwarf sheep raised intensively in Michael Okpara University of Agriculture Livestock Farm, Umudike, Abia state in the rainforest belt of Nigeria were evaluated over a ten-year period (1998-2007). The flock was fed cut-and-carry forages consisting mainly browse plants, legumes and grasses in addition to receiving 16% CP concentrate supplement formulated from maize, wheat offal, soya cake etc. Parameters investigated were prolificacy, types of births and pre-weaning mortality as influenced by seasons. Results showed that there were 207 lamb harvests resulting from 157 lambing delineated into 122 single, 20 twin and 15 triplet births. Prolificacy was 135%. Season had significant (P<0.05) effect on lambing with rainy and dry season figures as 69.7 and 30.3%, respectively; single, twin and triplet births were however not affected (P>0.05). Mortality was fairly high generally (35.00%) within the flock with pre- and post weaning values at 30 and 7%, respectively. Season also had significant effect (P<0.05) on mortality (pre- and post weaning values were 73.3 and 26.7% and 71.4 and 28.6% for the rainy and dry seasons, respectively). Causes of mortality were linked to still birth (14.86%), hypothermia (9.46%), pneumonia (17.57%), starvation (27.03%), weakness (10.81%) and unknown causes (20.27%). The population of WAD sheep could be enhanced through management practices that would reduce avoidable mortalities.